One Thousand and One Nights at the Transnational Crossroads - Sima AGHAZADEH (Cultural Intertexts, 2022)
One Thousand and One Nights - also known in English as the Arabian Nights - is a compilation of folkloric tales, with anonymous author(s), dating as far back as the 14th or 15th century but assumed to be rooted much earlier, perhaps the 10th century in its Arabic version and even earlier in its lost Persian embodiment. This authorless work was introduced to the West first in the 18th and later in the 19th century by its French and English Orientalist translators by whom it was brought to life reborn in an alien environment with radically different perceptions and receptions. Since then, The Nights has become one of the most global and yet misunderstood works across various artistic versions besides literature. The narrative framework tells us tales that are widely varied and spread in various regions with their historical and cultural backgrounds, including Persia, Arabia, India, Egypt, China, and so on. On this account, this paper aims to highlight that the multiplicity and hybridity of voices, histories, and cultures position the work at a transnational crossroads. Without dismissing the Oriental aspects of the work, this paper emphasizes that the adaptation and appropriation of such an elusive work with a convoluted history cannot be discussed authoritatively (either through Western Oriental or Post-Colonial or Islamic perspectives) when there is no one author or manuscript or no one culture and nation as a reference point. Each translation or adaptation helps the work expand its transnational network, interconnect old and new, East and West together, bridge differences and continue to address the questions of cultural transformation.